2020
DOI: 10.1038/s41598-020-59204-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the complete plastomes and the phylogenetic analysis of Paulownia species

Abstract: Paulownia species are important ecological, economic and ornamental species, but their phylogenetic relationship remains unclear, which seriously affects the development and utilization of these important resources. the complete chloroplast genomes of six Paulownia species were assembled by next-generation sequencing data. By adding two known Paulownia chloroplast genomes to these six assembled genomes, we performed the comparative analysis and phylogenetic tree reconstruction of Paulownia. the results indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 51 publications
0
24
0
Order By: Relevance
“…In general, previous studies showed that Ka/Ks values are usually less than one [ 68 ], because synonymous nucleotide substitutions occur more frequently than nonsynonymous substitutions. Additionally, most genes of the chloroplast genome evolved under purifying selection due to functional limitation during chloroplast genome evolution [ 69 , 70 , 71 , 72 ]. Furthermore, both the positive selection of the rbcL gene and the NADH dehydrogenase subunit genes were previously reported in several studies, which is related to temperature, drought, carbon dioxide concentration, and photosynthetic rate [ 71 , 72 , 73 , 74 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, previous studies showed that Ka/Ks values are usually less than one [ 68 ], because synonymous nucleotide substitutions occur more frequently than nonsynonymous substitutions. Additionally, most genes of the chloroplast genome evolved under purifying selection due to functional limitation during chloroplast genome evolution [ 69 , 70 , 71 , 72 ]. Furthermore, both the positive selection of the rbcL gene and the NADH dehydrogenase subunit genes were previously reported in several studies, which is related to temperature, drought, carbon dioxide concentration, and photosynthetic rate [ 71 , 72 , 73 , 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, most genes of the chloroplast genome evolved under purifying selection due to functional limitation during chloroplast genome evolution [ 69 , 70 , 71 , 72 ]. Furthermore, both the positive selection of the rbcL gene and the NADH dehydrogenase subunit genes were previously reported in several studies, which is related to temperature, drought, carbon dioxide concentration, and photosynthetic rate [ 71 , 72 , 73 , 74 ]. Positive selection is considered to be indicative of an adaptation to environmental change, ecological niche, or coevolutionary processes [ 73 , 75 ], and we can, thus, speculate that the selection patterns detected for the Rosaceae endemic taxa on Ulleung Island may be associated with adaptation to an oceanic climate in the insular setting.…”
Section: Resultsmentioning
confidence: 99%
“…Most plastome genes evolved under purifying selection due to functional constraints throughout the chloroplast genome evolution [ 48 , 49 , 50 , 51 ]. In 12 plastomes of the genus Hosta , we found that all but five genes (70 out of 75 genes) were under strong purifying selection with an average Ka/Ks ratio of <1.…”
Section: Discussionmentioning
confidence: 99%
“…Most genes of the plastome evolve under purifying selection due to functional limitations during the course of evolution [ 65 , 66 , 67 , 68 ]. In the five Fagus plastomes studied, nearly 7.8% of protein-coding genes, including two photosynthesis-related genes encoding NADH-dehydrogenase subunits ( ndhD and ndhJ ), two genes encoding DNA-dependent RNA polymerase ( rpoB and rpoC2 ), one self-replication-related gene encoding the ribosomal small subunit ( rps16 ), and two unknown genes ( ycf1 and ycf2 ), were under positive selection pressure.…”
Section: Discussionmentioning
confidence: 99%